Exploring Morphological Traits and Phytochemical Profiles of Natural Dye Plants in Gringsing Fabric: A Contextual Approach to Biology Education - Ayu Rai, I Gusti; Suanda, I.W.; Mirah, A.A.I.; Triyanti, N.K; Putu Rahayu Artini, Ni (UNIVERSITAS ISLAM NEGERI RADEN INTAN LAMPUNG, 2026)
Natural dyes are increasingly considered sustainable alternatives to synthetic textiles dyes, yet their use is often based on tradition rather than scientific understanding. This study explores the morphological traits and phytochemical profiles of plants used in Gringsing fabric and considers their relevance for biology education. A qualitative descriptive approach was applied to four species through field observation, interviews, and phytochemical screening of selected plant parts. The findings show that phenolics, tannins, and flavonoids are consistently present and play key roles in color formation and binding. Observable plant characteristics were closely linked to the distribution of these compounds, suggesting a clear scientific basis behind traditional practices. Integrating these findings into learning materials offers a meaningful way to connect biological concepts with local knowledge in classroom contexts. Eksplorasi Karakter Morfologi dan Profil Fitokimia Tanaman Pewarna Alami pada Kain Gringsing: Pendekatan Kontekstual dalam Pendidikan Biologi ABSTRAK: Pewarna alami semakin dipandang sebagai alternatif ramah lingkungan, namun penggunaannya masih banyak didasarkan pada pengalaman tradisional tanpa pemahaman ilmiah yang memadai. Penelitian ini mengeksplorasi karakter morfologi dan profil fitokimia tumbuhan pewarna pada kain Gringsing serta kaitannya dengan pembelajaran biologi. Pendekatan deskriptif kualitatif dilakukan terhadap empat spesies melalui observasi lapangan, wawancara, dan skrining fitokimia pada bagian tumbuhan tertentu. Hasil menunjukkan bahwa senyawa fenolik, tanin, dan flavonoid berperan penting dalam pembentukan dan pengikatan warna. Karakter morfologi yang tampak berkaitan dengan sebaran senyawa tersebut, menunjukkan adanya dasar ilmiah dalam praktik tradisional. Temuan ini dapat dimanfaatkan sebagai bahan pembelajaran kontekstual yang menghubungkan konsep biologi dengan kearifan lokal.